A Generalized Model of Administrative Decisions: An Experimental Test - Dickson, Gary W. (Management Science, 1970)
A model intended to predict decisions made from among alternatives having fixed characteristics is hypothesized and the experimental procedure used to test the model and the results of testing the model are presented. The model, which is based upon decision segmentation and disutility minimization, was tested in the framework of vendor selection decisions. The results indicate that the model was able to predict the vendor selections of the purchasing agent-subjects with a high degree of accuracy.